Theory of elasticity of the Abrikosov flux-line lattice for uniaxial superconductors: Parallel flux lines - Sardella, Edson [UNESP] (American Physical Society (APS), 1991)
In this paper, we consider the extension of the Brandt theory of elasticity of the Abrikosov flux-line lattice for a uniaxial superconductor for the case of parallel flux lines. The results show that the effect of the anisotropy is to rescale the components of the wave vector k and the magnetic field and order-parameter wave vector cut off by a geometrical parameter previously introduced by Kogan. © 1991 The American Physical Society.